An Investigation of the Integration of MOOC in Literature Classrooms Case Study: Second Year Students University of Laghouat Department of English Language - Zougari, Sarah; Boumediene, Houda (University of Ammar Theledji -Laghouat, 2020)
Teaching English as a foreign language has become a challenge due to the variety of techniques and methods of teaching as well as the diversity of learners‟ motivations and interests for learning. Therefore, instructors have to think about current ways to incorporate new strategies in order to promote their teaching process and reach their teaching goals. For this reason, the integration of Information CommunicationTechnology especially Massive Open Online Coursess became widely spread in so many fields including language learning/teaching and more particularly teaching literature. The latter represents that the use of MOOC helps in understanding of most of the difficult literary texts. Thus, the present study was conducted to evaluate technology-based instruction using MOOC as an educational tool in learning /teaching EFL literature to Second-year students at the University of Amar Thelidji, the specific objectives include evaluating students' outcomes and attitudes toward the incorporation of MOOC in the learning process. To attain the aim of the experimental study two research instruments were used, an experiment with second year students followed by two online questionnaires addressed to 9 teachers and 45 second year students. The findings of the study show that the integration of MOOCs made a suitable tool for promoting learning literature and support the argument which suggests that learners have profited from using MOOCs and they are getting more involved in the experience. Also, this tool enables both teachers to integrate online content and activities with face to face teaching, and learners to facilitate and reinforce literature studies. Based on this study, the integration of MOOC in literature class is a starting point for further research in blending MOOC in traditional settings to achieve a successful implementation of online content in a way that it facilitates the learning/teaching process